Analysis of 137Cs Radionuclide Content in Sediment in Musi Watershed Using Gamma Spectrometer and its Affecting Factors - T. A. Jaya; A. Mara; G. F. Amri (Atom Indonesia, 2021)
The concentration of the radionuclide 137Cs on sediment in watershed in Palembang has been analyzed. This study aims to determine the influence of sampling location and the water quality indicators of water pH, sediment pH, conductivity, turbidity, and sediment type on the concentration of 137Cs and to determine the distribution pattern of 137Cs in sediments. Sampling was conducted at seven stations spaced approximately 5 km apart, placed from the western end to the eastern end  of the Musi river segment located within Palembang City.Sediment samples were prepared and their 137Cs contents were measured with gamma spectrometry. The results showed that their 137Cs concentrations ranged from below MDC (minimum detectable concentration) to 1.51 Bq/kg. This was within the 1×103 Bq/kg limit set by the quality standard. The varied and very low concentrations of 137Cs are thought to have originated from global fallout. The location point of sampling affects the concentration of radionuclide 137Cs while the characteristics of water quality are do not. The 137Cs concentration spread pattern in Musi sediment is influenced by tidal currents and river morphology.